A Formação de Professores de Português Língua estrangeira/segunda Língua na Universidade Federal do Espírito Santo - Mello, Renata Rocha Vieira de (2021)
We have witnessed, especially since the 1990s, an intense development in the area of Portuguese as a Foreign Language and/or Second Language (PFL/L2), in terms of research, events, publications and language policies (ALMEIDA FILHO, 2011a, 2011b). The lear